2012
DOI: 10.1063/1.4768916
|View full text |Cite
|
Sign up to set email alerts
|

Slowing down the speed of terahertz guiding modes of a metal air-gap waveguide by using a coupled plasmonic cavity

Abstract: Articles you may be interested inMinimization of reflection at the boundaries of a finite-size coupled terahertz cavity in a metal air-gap waveguide Properties of defected one-dimensional terahertz plasmonic crystal films in a metal air-gap waveguide J. Appl. Phys. 110, 093101 (2011); 10.1063/1.3658255Photonic band anti-crossing in a coupled system of a teraherz plasmonic crystal film and a metal air-gap waveguideWe present numerical and experimental demonstration of slowing down the speed of terahertz guiding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The group velocity (group index) noticeably decreases (increases) to less (larger) than 0.01c (100) as a frequency approaches to the band edges. The oscillatory behavior in the transmission spectra, dispersion relation and group velocity curve, was also observed in different coupled resonator systems and could be reduced by modifying the input and output interfaces of the couple resonator system [7,[25][26][27][28][29]. For the coupled resonator system considered in this study, a practical way to reduce the troublesome reflections is introducing rods at the ends of the coupled resonator.…”
Section: Resultsmentioning
confidence: 74%
“…The group velocity (group index) noticeably decreases (increases) to less (larger) than 0.01c (100) as a frequency approaches to the band edges. The oscillatory behavior in the transmission spectra, dispersion relation and group velocity curve, was also observed in different coupled resonator systems and could be reduced by modifying the input and output interfaces of the couple resonator system [7,[25][26][27][28][29]. For the coupled resonator system considered in this study, a practical way to reduce the troublesome reflections is introducing rods at the ends of the coupled resonator.…”
Section: Resultsmentioning
confidence: 74%
“…However, it was observed that unwanted reflections at the boundaries of a finite-size CZBR give rise to unnecessary finite-size effects, such as strong Fabry-Pérot oscillations in the transmission spectrum and variations in the group velocity curve. Hence finite-size effects, which are commonly observed in various coupled resonator systems [3,28], ruin the performance of a slow light device. Therefore, an efficient and practical method to reduce unwanted reflections at the PC-CZBR interface is required in order to increase the possibility of the application of slow self-collimated beams in PCs.…”
Section: Introductionmentioning
confidence: 99%